4p-7=2p-3

Simple and best practice solution for 4p-7=2p-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4p-7=2p-3 equation:


Simplifying
4p + -7 = 2p + -3

Reorder the terms:
-7 + 4p = 2p + -3

Reorder the terms:
-7 + 4p = -3 + 2p

Solving
-7 + 4p = -3 + 2p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-2p' to each side of the equation.
-7 + 4p + -2p = -3 + 2p + -2p

Combine like terms: 4p + -2p = 2p
-7 + 2p = -3 + 2p + -2p

Combine like terms: 2p + -2p = 0
-7 + 2p = -3 + 0
-7 + 2p = -3

Add '7' to each side of the equation.
-7 + 7 + 2p = -3 + 7

Combine like terms: -7 + 7 = 0
0 + 2p = -3 + 7
2p = -3 + 7

Combine like terms: -3 + 7 = 4
2p = 4

Divide each side by '2'.
p = 2

Simplifying
p = 2

See similar equations:

| 18+6x=2y | | 2y+18=6x | | 3.5+q=7.8 | | -z^2+z+14=0 | | -3x-5=-4x+3 | | 3x^2+6x-360=0 | | 4x+21=12x-51 | | 5=10+4.9x-4.9x^2 | | -74-7x=137-37x | | 6a+2(4a+1)=-5 | | -18=8p-(33-2p) | | -8f=-184 | | 11x+11=10x-21 | | A^2-4A+4=0 | | 16(2x-5)=4(8x+8) | | 36-(5a+19)=-3 | | 9x-12=8x+2 | | 12y=6y+9 | | 0=-9m-18 | | 7+13s-2=9s+25-6s | | m-(4+2m)+3=2m+2 | | -6x+8=62 | | P^2+6=127 | | -107+k=-99 | | 12x+29=3x+254 | | x^4+2x^2=3x | | -16=y-25 | | 4y+11y=120 | | 102-6x=12x+20 | | [2x-3]=6 | | 28-k=-19 | | k-49=-62 |

Equations solver categories